Security management in mobile cloud computing - Laursen, Finn (Advances in information security, privacy, and ethics (AISPE) book series, 2017)
This book explores the difficulties and challenges of securing user data and information on mobile cloud platforms, investigating a variety of protocols and architectures that can be used to design, create, and develop security mechanisms.